Creating Hot Incentives : The case of Luleå Energi's new price model for district heating - Sundström, Kristoffer (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2019)
In September 2017, Luleå Energi introduced a new price model on district heating for their enterprise customers with the intention to create stronger incentives for energy efficiency measures, and provide price signals that better correspond to the underlying production costs. The purpose of this thesis is to investigate whether the intentions of Luleå Energi has been fulfilled, not the least in the form of improved energy efficiency among the affected enterprises. This thesis also provides a theoretical assessment of the new price model through conducting a literature review. The empirical analysis builds on theories addressing issues such as bounded rationality, profit maximizing firms, uncertainty, and imperfect information. The results show that the new price model may have been hindered by bounded rationality amongst the enterprise customers, and the overall low price level of district heating services in Luleå. Results also show that even if the new price model is fairly good at creating incentives, it could probably become more effective if the effect price component were based on enterprise customers current effect usage rather than the enterprise customers effect usage during the previous winter season. I september 2017 introducerade Luleå Energi en ny prismodell för deras fjärrvärme tjänster gentemot företagskunder med intentionen att skapa starkare incitament för energieffektiviseringsåtgärder och förse marknaden med prissignaler som motsvarar de underliggande produktionskostnaderna. Syftet med denna uppsats är att undersöka huruvida Luleå Energi’s intentioner har blivit uppfyllda, inte minst i form av energieffektiviseringsåtgärder. Studien kommer också att, med hjälp av en litteraturstudie, genomföra en teoretisk bedömning av den nya prismodellen. Studien applicerar teorier som begränsad rationalitet, vinstmaximerande företag, osäkerhet och ofullständig information. Resultaten visar att den nya prismodellen eventuellt hindras av begränsad rationalitet hos kunderna, och den överlag låga prisnivån ...